2018
DOI: 10.3390/mca23040080
|View full text |Cite
|
Sign up to set email alerts
|

CFD Investigation of the Effect of the Feed Spacer on Hydrodynamics in Spiral Wound Membrane Modules

Abstract: Spacers are designed to create a feed channel, but they are also obstacles to the flow in spiral wound membrane modules. The geometry of the feed spacer influences the flow pattern, which was investigated by using a three-dimensional Computational Fluid Dynamics (CFD) model. For the conventional feed spacer, unavoidable disadvantages were caused by its line contact with the membrane. The pillar-like feed spacer was designed to achieve area contact, which made it possible to enhance the porosity and minimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In view of this, CFD modelling is often preferred over experimental tests for predicting the performance of novel spacer geometric designs. Hence, numerical studies of several complex spacer geometries can be found in the literature, such as the triply periodic minimal surface (TPMS) structure ( Figure 3 b) [ 52 , 60 , 63 , 64 , 65 ], perforated spacer geometries ( Figure 3 c) [ 55 ] and submerged spacers with column nodes ( Figure 3 d) [ 56 , 58 , 66 ]. Although a previous review [ 18 ] has discussed the criteria for optimising spacer design, most designs are still restricted to simple cylindrical or two-layer spacer geometries.…”
Section: Development Of New Spacer Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, CFD modelling is often preferred over experimental tests for predicting the performance of novel spacer geometric designs. Hence, numerical studies of several complex spacer geometries can be found in the literature, such as the triply periodic minimal surface (TPMS) structure ( Figure 3 b) [ 52 , 60 , 63 , 64 , 65 ], perforated spacer geometries ( Figure 3 c) [ 55 ] and submerged spacers with column nodes ( Figure 3 d) [ 56 , 58 , 66 ]. Although a previous review [ 18 ] has discussed the criteria for optimising spacer design, most designs are still restricted to simple cylindrical or two-layer spacer geometries.…”
Section: Development Of New Spacer Designsmentioning
confidence: 99%
“…At the time of writing, CFD studies of RO processes have mainly focused on either 2D unsteady state [ 74 , 75 , 76 , 77 , 78 , 79 ] or 3D steady state [ 51 , 54 , 57 , 66 , 80 , 81 , 82 ]. It is worth noting that the ability of 2D and 3D CFD modelling for predicting mass transport and concentration polarisation has been well established in the literature [ 46 , 68 , 74 , 83 ].…”
Section: Existing Cfd Models and Their Challengesmentioning
confidence: 99%
“…Numerical studies have proposed efficient spacer designs, geometries, and arrangements (Amokrane et al, 2015;Han et al, 2018;Kavianipour et al, 2017;Koutsou et al, 2007;Saeed et al, 2015;Saeed et al, 2012). The circular and elliptical shaped filaments reduced the hydraulic resistance compared to the other spacer geometries while the triangular and square filaments increased the mass transfer (Ahmad and Lau, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The flows in the ozone contactor were considered isothermal, and the Grace Drag force model was applied for the interphase momentum transfer and turbulent dispersion [34]. The turbulence of the dispersed gas phase was modeled using a zero-equation model for the dispersed phase, and bubble-induced turbulence was considered based on [35]. The transport equation was also used to describe the evolution of ozone concentration and total coliforms in the fluid, and to account for any reactions that may occur.…”
Section: Cfd Equations and Assumptionsmentioning
confidence: 99%